Celebrities, heroes and champions : Popular politicians in the age of reform, 1810-67 - Morgan, Simon, 1974- (Book collections on Project MUSE., 2021)
Celebrities, heroes and champions examines the popular politician in British and Irish society from the Napoleonic Wars to the Second Reform Act. Covering a range of political movements, it offers a unique perspective on contemporary political culture including the connections between popular politics and an evolving culture of celebrity.